The Influence of Problem Based Learning and Discovery Learning Models Assisted by Learning Video Media on Student Learning Results and Activities on Redox Reaction - Harahap, Aisyah Sari Dewi; Jasmidi, Jasmidi (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
This study aims to analyze the differences in learning outcomes and student engagement between the Problem Based Learning (PBL) model and the Discovery Learning (DL) model supported by learning videos, as well as to identify the relationship between these factors in the context of redox reactions at MAS Muallimin Univa Medan. The sample consists of two classes randomly selected from the Class X MIA population: the PBL class (X MIA 2) and the DL class (X MIA 3). The research instruments included a multiple-choice test with 20 valid and reliable questions to assess learning outcomes and an observation sheet to evaluate student engagement. Data were analyzed using independent sample t-tests. Results indicated that the PBL class had lower scores in both engagement and learning outcomes compared to the DL class. Statistical analysis revealed significant differences in engagement and learning outcomes (α < 0.05), with a positive correlation between student engagement and learning outcomes. The conclusion of this study is that there are differences in learning outcomes and engagement between the two models, as well as a significant relationship between student activity and learning success, with contribution rates for engagement reaching 64.3% and 24.9%.Keywords: Learning Outcomes, Learning Activities, Problem Based Learning, Discovery Learning, Learning Videos¸ Redox Reactions.DOI: 10.23960/jppk.v13.i3.30701